2020
DOI: 10.1371/journal.pone.0229390
|View full text |Cite
|
Sign up to set email alerts
|

Dual-locus DNA metabarcoding reveals southern hairy-nosed wombats (Lasiorhinus latifrons Owen) have a summer diet dominated by toxic invasive plants

Abstract: Habitat degradation and summer droughts severely restrict feeding options for the endangered southern hairy-nosed wombat (SHNW; Lasiorhinus latifrons). We reconstructed SHNW summer diets by DNA metabarcoding from feces. We initially validated rbcL and ndhJ diet reconstructions using autopsied and captive animals. Subsequent diet reconstructions of wild wombats broadly reflected vegetative ground cover, implying local rather than long-range foraging. Diets were all dominated by alien invasives. Chemical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Five GSs (progoitrin, sinigrin, glucotropaeolin, 4-hydroxyglucobrassicin and 9-(methylsulfonyl) hydroxy nonyl glucosinolate) were detected in the current study. On the other hand, gluconapin, brassicanapin, erucin, glucoberteroin, glucoerucine and glucoraphanin which were reported in Spanish and Australian C. annua [ 38 , 39 ] were not detected.…”
Section: Resultsmentioning
confidence: 95%
“…Five GSs (progoitrin, sinigrin, glucotropaeolin, 4-hydroxyglucobrassicin and 9-(methylsulfonyl) hydroxy nonyl glucosinolate) were detected in the current study. On the other hand, gluconapin, brassicanapin, erucin, glucoberteroin, glucoerucine and glucoraphanin which were reported in Spanish and Australian C. annua [ 38 , 39 ] were not detected.…”
Section: Resultsmentioning
confidence: 95%
“…These degraded habitats harboured plant species including Potato weed, Ward's weed, and Onion weed, and contain toxic plant defence compounds (eg. pyrrolizidine alkaloids) [31,60]. Previous work on other herbivorous mammals has demonstrated that the gut microbiota can detoxify plant defence compounds for the host [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…The area consists of remnant mallee eucalypt woodland with a chenopod and grassland understory composed of a variety of introduced weeds, native grasses and chenopods. The diet of wombats in this area is made up largely of introduced weed species including thread iris ( Moraea setifolia ), wards weed ( Carrichtera annua ) and burr medic ( Medicago minima ), along with remnant chenopods and a few native grass species [ 31 ]. Except immediately after rain, no free water is available at these sites.…”
Section: Methodsmentioning
confidence: 99%
“…These degraded habitats harboured plant species including, Potato weed, Ward's weed, and Onion weed, and contain toxic plant defence compounds (eg. pyrrolizidine alkaloids) [59,31]. Previous work on other herbivorous mammals has demonstrated that the gut microbiota can detoxify plant defence compounds for the host [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Active weed management is undertaken at this site. Native grasses and forbs, the dominant component of wombat diet in this region, ourish at this site and include many Stipia, Hyalosperma, Silene, Rytidiosperma and Sida spp, and a wide variety of Chenopodiaceae (saltbush -Atriplex, Enchylaena and Rhagodia spp, and bluebush -Maireana spp) among others [31]. Except immediately after rain, no free water is available at this site.…”
Section: Intact Habitat -Wonga Stationmentioning
confidence: 99%